Ultrasound Mediated Cellular Deflection Results in Cellular Depolarization. Issue 2 (7th November 2021) - Vasan, Aditya; Orosco, Jeremy; Magaram, Uri; Duque, Marc; Weiss, Connor; Tufail, Yusuf; Chalasani, Sreekanth H; Friend, James
Abstract: Ultrasound has been used to manipulate cells in both humans and animal models. While intramembrane cavitation and lipid clustering have been suggested as likely mechanisms, they lack experimental evidence. Here, high‐speed digital holographic microscopy (kiloHertz order) is used to visualize the cellular membrane dynamics. It is shown that neuronal and fibroblast membranes deflect about 150 nm upon ultrasound stimulation. Next, a biomechanical model that predicts changes in membrane voltage after ultrasound exposure is developed. Finally, the model predictions are validated using whole‐cell patch clamp electrophysiology on primary neurons. Collectively, it is shown that ultrasound stimulation directly defects the neuronal membrane leading to a change in membrane voltage and subsequent depolarization. The model is consistent with existing data and provides a mechanism for both ultrasound‐evoked neurostimulation and sonogenetic control. Abstract : With the help of a new method for imaging cell membrane motion, high‐speed digital holographic microscopy, membrane deformation responsible for the direct depolarization of membranes that lead to action potential generation in nerve cells is observed. A complete model of the phenomena has been devised, producing voltage spiking and oscillation predictions similar to patch clamp measurements.